2020
DOI: 10.1002/cae.22371
|View full text |Cite
|
Sign up to set email alerts
|

Effect of virtual reality technology on the teaching of urban railway vehicle engineering

Abstract: The real key structures of urban railway vehicle are costly and dangerous, but students majoring in relevant fields have to acquire skills needed to operate the key structures to get good jobs or do academic research easily. The virtual reality (VR) technology, which has been used in many fields, can provide students with a unique learning experience. The purpose of this paper is to investigate the impact of VR on the operational skills and cognitive load in students studying urban railway vehicle engineering.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…VR technology plays a positive part in the students' acquisition of operational skills. The virtual reality learning environment (VRLE) helped reduce the cognitive load in the students when they were performing experiments [38]. A Petri net (PN)‐based approach is proposed to support VR model behavior programming.…”
Section: Literature Reviewmentioning
confidence: 99%
“…VR technology plays a positive part in the students' acquisition of operational skills. The virtual reality learning environment (VRLE) helped reduce the cognitive load in the students when they were performing experiments [38]. A Petri net (PN)‐based approach is proposed to support VR model behavior programming.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The application of virtual reality technology in teaching is mainly to make participants vividly feel the scenes similar to reality, and bring a more positive impact to participants’ learning. This technology has gradually been studied in training, engineering education, science education, engineering laboratory, etc 11 14 . The virtual simulation platform can provide convenient interactive learning of 3D models by using remote laboratory, computer, and web-based simulation 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%
“…The instructional designer can’t have a direct influence on the internal cognitive load, but the external cognitive load and related cognitive load are related to the instructional designer, and the three types of load are superimposed on each other 31 , 32 . Yang et al developed a virtual simulation teaching platform for urban rail transit and studied the influence of simulation teaching on students’ knowledge learning and cognitive load 11 . Researchers have found that using a virtual simulation platform to improve teaching design can help reduce students’ cognitive load and promote effective learning 11 , 17 , 33 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For large‐scale and complex engineering systems with high voltage and risk, practical courses are difficult to be conducted in traditional laboratories at universities, and students often do not have the opportunity to visit a real engineering project. Virtual simulation practical teaching has become a new kind of teaching mode with the development of virtual reality and computer technologies [6,13,16,19,24]. Virtual simulation technology provides clear visions and simulation analysis of experiments that cannot be carried out in traditional laboratories [3‐5,17,18,20,22].…”
Section: Introductionmentioning
confidence: 99%